2022
DOI: 10.1002/ca.23996
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional development and asymmetry of the corpus callosum in the 0–18 age group: A retrospective magnetic resonance imaging study

Abstract: Most of the corpus callosum (CC) developmental studies are concerned with its twodimensional structure. Linear and area measurements do not directly assess the CC size but estimate the overall structure from the cross-sectional image. This study investigated age-and sex-related changes in volumetric development and asymmetry of CC from birth to 18. For this retrospective study, we selected 696 patients (329 [47.27%] females) with both 3D-T1-weighted sequence and normal radiological anatomy from patients 0-18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Within a similar age range (8–30 years), Koolschijn and Crone (2013) reported larger cerebellar grey matter volume in males than in females (controlling for ICV). The sparse sex effects in the QTAB dataset are similar to the results in adolescents reported by Isiklar et al (2023) and Gaiser et al (2024). However, these results are inconsistent with the findings of Rice et al (2023), in which a greater number of regions showed significant sex effects (controlling for ICV) in similarly aged participants.…”
Section: Discussionsupporting
confidence: 88%
“…Within a similar age range (8–30 years), Koolschijn and Crone (2013) reported larger cerebellar grey matter volume in males than in females (controlling for ICV). The sparse sex effects in the QTAB dataset are similar to the results in adolescents reported by Isiklar et al (2023) and Gaiser et al (2024). However, these results are inconsistent with the findings of Rice et al (2023), in which a greater number of regions showed significant sex effects (controlling for ICV) in similarly aged participants.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have con rmed that CC played an important role in regulating motor and non-motor functions in PD [14][15][16]. Nevertheless, CC is not a homogeneous component which the segments connecting to different cortical regions vary in ber size and density [13] and it may develop asymmetrically during growth [17]. Therefore, we speculate that differences in degenerative patterns of CC may be one of the potential mechanisms affecting the nonmotor symptoms and prognosis in PD patients with unilateral onset.…”
Section: Introductionmentioning
confidence: 99%